Mobile On-Call: Design of a Non-Invasive, Non-Intrusive, Personal Vital Signs Monitor - Zernask-Cebek, Kirsten (My University, 2010)
Currently, there are limited resources in place for patients who are recovering from illness and surgeries to be monitored at home while trying to resume or maintain a normal lifestyle. The Mobile On-Call system is a low-cost, low power device developed to address these issues. This device is intended to enable greater independence for those patients, while still offering real-time monitoring of their vital signs, and an immediate connection to healthcare. This project delivers a cell phone based program to actively monitor and assess a user‟s health based on three vital signals; electrocardiogram, blood pressure and body temperature. The results of the analysis are presented to the user via a graphical interface, and communicated to a physician or healthcare practitioner if deemed necessary, over an available cell phone network. It implements algorithms adapted to a mobile phone platform to compress and store the data efficiently.
Keywords: wireless; Bluetooth; data compression; lossless; biomedical monitoring; Biomedical; Electrical and Computer Engineering; Biomedical